Industrial training final report: Sam Meerkat (M) Sdn. Bhd. / Muhammad Fitri Syawal Ariff - Ariff, Muhammad Fitri Syawal (Universiti Teknologi MARA, Pulau Pinang, 2024)
Sam Engineering & Equipment (M) Berhad, a venerable presence in the corporate landscape since its establishment in 1948, stands as a distinguished holding company specializing in the provision of comprehensive corporate management services. The firm strategically positions itself as a key player in precision machining, equipment integration, and automation solutions, with a specific focus on meeting the discerning needs of the aerospace and equipment industries. A pivotal juncture in its corporate trajectory occurred when SAM made its debut on the ACE Market in 1995, subsequently achieving a commendable elevation to the Main Market of Bursa Malaysia in 1999. This strategic progression underscores SAM's commitment to continuous growth and an augmented market presence within the broader financial landscape. Functioning as a subsidiary of Singapore Aerospace Manufacturing Pte Ltd (SAM), the company leverages the esteemed reputation of its parent entity, recognized as a leading manufacturer of critical aero-engine components serving the sophisticated requirements of the international aerospace market. SAM's distinguished clientele includes industry behemoths such as Boeing, GE Aircraft Engines, GKN Aerospace Services, Goodrich, and various other prominent aerospace original equipment manufacturers.